2022
DOI: 10.1002/sd.2373
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of citizen science approach for monitoring Sustainable Development Goal 6: Clean water and sanitation for an Indian city

Abstract: The United Nations acknowledges that action in one of the 17 Sustainable Development Goals (SDGs) will impact outcomes in others and that development should interact the social, economic, and environmental sustainability. Many countries have prioritized goals and targets based on their current progress and the prosperity of their people. This article focused on SDG 6: Clean water and sanitation, especially the first two (6.1 and 6.2) out of eight targets. The author has considered SDG 6, a critical goal to foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 70 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…These changing expectations are usually investigated with a ‘citizen science’ approach to ensure that the organisation adapts to first‐hand user views (Malhotra et al, 2017). Citizen science describes a method of public participation in scientific investigations wherein members of the public provide their real‐world sensing as (a) scientific data, and (b) directions for inquiry (Millar & Searcy, 2019; Venkatesh & Velkennedy, 2022).…”
Section: Strategy and Its Principlesmentioning
confidence: 99%
“…These changing expectations are usually investigated with a ‘citizen science’ approach to ensure that the organisation adapts to first‐hand user views (Malhotra et al, 2017). Citizen science describes a method of public participation in scientific investigations wherein members of the public provide their real‐world sensing as (a) scientific data, and (b) directions for inquiry (Millar & Searcy, 2019; Venkatesh & Velkennedy, 2022).…”
Section: Strategy and Its Principlesmentioning
confidence: 99%
“…Almeida et al (2018) and Martínez‐Córdoba et al (2021) study the implementation of SDG 11 in Brazilian and Spanish municipalities, respectively. Pereira et al (2021) explore SDG 3 in Brazilian municipalities, and Venkatesh and Velkennedy (2023) focus on SDG 6 in an Indian municipality.…”
Section: Literature Review: the Role Of The Public Sector In The Impl...mentioning
confidence: 99%
“…The geographical detail of the study area is shown in Figure 2. Table 1 presents the four zones in the study area (Melapalayam, Thachanallur, Tirunelveli, and Palayamkottai) with a total number of 55 municipal wards for administrative purposes (Venkatesh & Velkennedy, 2022).…”
Section: Study Areamentioning
confidence: 99%
“…The approximate geographical coordinate at the centroid point of the corporation area is 8 43 0 22 00 N and 77 43 0 0.84 00 E. The geographical detail of the study area is shown in Figure2. Table1presents the four zones in the study area (Melapalayam, Thachanallur, Tirunelveli, and Palayamkottai) with a total number of 55 municipal wards for administrative purposes(Venkatesh & Velkennedy, 2022).3 | DATA SOURCE AND METHODIndicator 11.1.1 for safe and affordable housing from the 2030 agenda needs the data to quantify the population proportion lives in slums, informal settlements, and inadequate housing to implement relevant programs and policies to ensure all people have access to adequate housing and upgradation of slums (United Nations Human Settlement Programme (UN-Habitat), 2018). UN-Habitat defines a slum as a household with a few or more people living in the same confined space that lacks one or more amenities like durable housing, sufficient living area, access to improved water, improved sanitation facilities, and secure tenure (UN Habitat, 2016).…”
mentioning
confidence: 99%